Supervision of Supervisors in Improving the Performance of Professional Teachers Raudhatul Athfal in Jayapura City - Zunaidah, Hanik; Rokhmah, Siti (Institut Agama Islam Negeri Sorong, 2023)
Early religious education through the Raudhatul Athfal level is essential. The existence of Raudhatul Athfal teachers in Jayapura City amounts to 31 people spread across 6 Raudhatul Athfal with one supervisor; their existence as educators and professional education must continue to be improved. A supervisor under the Ministry of Religious Affairs is also a supervisor in 10 madrasas in the Jayapura City area. This study aims to describe the supervisor's strategy for improving the performance of professional teachers in Raudhatul Athfal Jayapura City. The research uses a qualitative approach with case study research—collection techniques through interviews, participatory observation, and documentation studies. The results showed that there are three strategies carried out by supervisors of Raudhatul Athfal of the Ministry of Religious Affairs of Jayapura City in improving the performance of RA teachers in Jayapura City through 1) the preparation of supervision programs by involving fellow elementary level supervisors, namely Islamic Education supervisors at the kindergarten-elementary level, 2) in the implementation of supervision always coordinates with the Chairman of IGRA Jayapura City KKGRA management Jayapura City. 3) Discuss with all teachers of Raudhatul Athfal.